Relationship between Employees' Attitudes and Error Rates in Public Welfare Programs - Petty, M. M.; Bruning, Nealia S. (Academy of Management Journal, 1980)
The article presents a study that explores the relationships between objective measures of organizational effectiveness and employees' attitudes concerning job satisfaction and employees' role stress in labor intensive public welfare agencies. The author notes three programs involved in the study: Aid to Families with Dependent Children (AFDC), Medicaid, and Food Stamps. The results of the study support the hypotheses that effective administration of the AFDC program is dependent on employee satisfaction.